2019
DOI: 10.1111/jvh.13165
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alpha treatment leads to a high rate of hepatitis B surface antigen seroconversion in Chinese children with chronic hepatitis B

Abstract: Chronic hepatitis B virus (HBV) infection (CHB) in children remains a public health challenge despite significant success in programme is established to prevent mother‐to‐child transmission. In particular, CHB in Chinese children are mostly acquired through vertical transmission, which differs from the common infection route reported in other countries and regions. This situation has resulted in a high endemic prevalence of CHB in Chinese adults. Thus, successful treatment of children with CHB will prevent the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Studies have reported that children and adolescents, especially the younger children, seemed to have higher rates of SR comparing to adults (19)(20)(21), which was possibly due to the relatively short incubation time of HBV and the less exhausted HBV-speci c immune response of the host (22,23). Higher level of ALT was an independent favorable factor for HBeAg SR, which were also in line with former studies (24,25).…”
Section: Discussionsupporting
confidence: 84%
“…Studies have reported that children and adolescents, especially the younger children, seemed to have higher rates of SR comparing to adults (19)(20)(21), which was possibly due to the relatively short incubation time of HBV and the less exhausted HBV-speci c immune response of the host (22,23). Higher level of ALT was an independent favorable factor for HBeAg SR, which were also in line with former studies (24,25).…”
Section: Discussionsupporting
confidence: 84%
“…Our findings confirmed a relatively high HBsAg loss rate of 36.4% (4/11) in the IFN‐based therapy group after a median follow‐up of 28.0 months. The rate falls into the reported ranges of 8.9%–83% with IFN‐based therapy after a maximum follow‐up of 13 years 12–14,26,27 . Whereas the effects of NAs are less studied.…”
Section: Discussionmentioning
confidence: 89%
“…In our study, lower HBsAg levels at baseline were positively associated with both HBeAg and HBsAg SR, which similarly indicated the value of quantitative HBsAg in guiding antiviral therapy in CHB children and adolescents. Moreover, younger age(< 6 years) was also a favourable factor for both HBeAg and HBsAg SR. Studies have reported that children and adolescents, especially younger children, seemed to have higher rates of SR than adults [ 24 26 ], which is possibly due to the relatively short incubation time of HBV and the less exhausted HBV-specific immune response of the host [ 27 , 28 ]. A higher level of ALT was an independent favourable factor for HBeAg SR, which was also in line with previous studies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%